Altered slow axonal transport and regeneration in a myelin-deficient mutant mouse: the trembler as an in vivo model for Schwann cell-axon interactions - de Waegh, S (J Neurosci, 1990)
The thickness of the myelin sheath in normal myelinated nerve is proportional to the diameter of the axon. In the demyelinating mutant mouse, Trembler, not only is the thickness of the myelin sheath reduced, but the caliber of associated axons is smaller. This correlation suggests that the interaction between axons and Schwann cells may affect the shape and function of axons as well as properties of myelin. Since axonal diameter depends in part on the cytoskeleton and its movement with slow axonal transport, we have compared the properties of slow transport in the sciatic nerve of control and Trembler mice. Studies of the sciatic nerve of normal mice showed that the rates for proteins moving in slow component a (SCa) and slow component b (SCb) are similar to those previously measured in rat. In Trembler mice, tubulin was transported significantly faster than in control mice, with a rate of 1.73 mm/d for Trembler compared to 1.56 mm/d in the control. In contrast, the rate for neurofilament proteins was significantly slower in the Trembler (1.15 mm/d compared to 1.38 mm/d in the control). The majority of proteins in SCb were also transported slower in Trembler than control: actin and calmodulin were transported at 2.29 mm/d as compared to 2.73 mm/d in control, while spectrin and clathrin were transported at 2.01 and 2.43 mm/d, respectively, as compared to 2.54 mm/d in control. The importance of slow axonal transport in regeneration has been suggested by the clear correlation between the rates of regeneration and the rates of SCb. Therefore, we evaluated regeneration of motor axons in Trembler mice to determine whether the regenerative response was affected by deficient Schwann cells. A slower regeneration rate was found in the Trembler (1.7 mm/d) motor axon when compared to the control (2.29 mm/d), but elongation of fibers in regeneration began after a shorter delay in the Trembler (1.6 d) than in control (2.5 d). Thus, deficient Schwann cells and poor myelination appear to affect both quantitative and qualitative properties of slow axonal transport. These changes lead to alterations in the morphological and physiological properties of affected axons.